A Sociolinguistic Approach to ELT: Perspectives from English Teachers - Nurmaisa; Arsyad, Safnil (UNIB Press, 2022)
The use of English seldom make students have a bad ability to speak and comprehend English as their teacher wants. It caused the students can not understand what their teacher has explained because they just have little vocabulary in English. Besides, the text in the students' book used foreign narratives, and foreign activities so that the students can not understand and comprehend the context of the book itself. Because of the condition, the teacher needs to approach to inform their students about English itself. That is why the sociolinguistic approach is needed in that condition because it can make students understand and comprehend easily the context of their English book. Therefore, this study is the gap to know teachers' perspectives on the use of the sociolinguistic approach in ELT and hindering that the teachers found in the implementation sociolinguistic approach. This study used descriptive qualitative research with 26 participants of English teachers. The findings of this study showed that sociolinguistics gave positive perspectives and benefits to the students.